Student dropout in production engineering: perspective of decision-making factors under a multicriteria approach - Oliveira; Mattos, Aliomar Lino; Rocha, Alessandro Roberto; Santos, Diego Vieira dos; Gonçalves, Wellington (Brazilian Journal of Production Engineering, 2020)
With the expansion of vacancies in federal universities in Brazil, evasion also increases, which presumes a adversity to be studied with priority by management. Within this context, this work aimed to prioritize possible causes that lead Production Engineering students to evade. For that, an Analytic Hierarchy Process (AHP) method was used to operationalize the methodological approach. As a research unit, a federal public institution was used. The results showed that the factor related to the attribute not identifying with the course has the greatest importance, with other important factors that are closely interconnected. It is worth mentioning that the literature presents results under the eyes of those who have already escaped, and not in the eyes of those who are still studying, nor the intensity of these reasons, something that was accomplished in this study.